2008
DOI: 10.1053/j.gastro.2008.05.046
|View full text |Cite|
|
Sign up to set email alerts
|

Androgen Receptor Is a New Potential Therapeutic Target for the Treatment of Hepatocellular Carcinoma

Abstract: Our data point to AR, but not androgens, as a potential new and better therapeutic target for the battle of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
242
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(256 citation statements)
references
References 35 publications
12
242
1
1
Order By: Relevance
“…Because the occurrence of chemically induced liver cancer is delayed in AR knockout mice, AR itself clearly behaves as a tumor-promoting gene for HCC. 7 Our previous study showed that HBx could enhance the transcriptional activity of AR, which leads to an increased risk of HCC. 8 The current study further disclosed a new role of AR in liver carcinogenesis, namely the activation of HBV transcription and replication.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because the occurrence of chemically induced liver cancer is delayed in AR knockout mice, AR itself clearly behaves as a tumor-promoting gene for HCC. 7 Our previous study showed that HBx could enhance the transcriptional activity of AR, which leads to an increased risk of HCC. 8 The current study further disclosed a new role of AR in liver carcinogenesis, namely the activation of HBV transcription and replication.…”
Section: Discussionmentioning
confidence: 98%
“…5,6 In AR knockout mice, the development of chemically induced HCC was delayed and the mice had fewer tumors. 7 These studies indicate that the AR axis is involved in hepatocarcinogenesis, and an active AR pathway may augment HCC risk. Consistent with this, we recently showed that HBV X protein (HBx) can enhance the transcriptional activity of AR in a ligand concentration-dependent manner, which may explain the male predominance of HBV-related HCC.…”
mentioning
confidence: 88%
“…The androgen pathway can increase the transcription of HBV through direct binding to the ARE sites in HBV enhancer I, leading to a higher HBV titer in male carriers and increased risk of HCC [53]. These facts together suggest that the targeting of AR might be developed as a new therapeutic strategy against HBV-related HCC [54].…”
Section: Androgen Receptor-mediating Signaling In Hbvrelated Hepatocamentioning
confidence: 99%
“…Ma et al [54] reported that mice lacking hepatic AR developed later and less HCC than their wild-type littermates with comparable serum testosterone in both males and females when using the Cre-Lox conditional knockout mouse model injected with carcinogen and that AR may promote hepatocarcinogenesis via increased cellular oxidative stress and DNA damage, as well as by suppression of p53-mediated DNA damage sensing/repairing system and cell apoptosis. Recently, it has been shown that vertebrae forkhead box A (Foxa) factors and their targets estrogen receptor (ERα) and/or AR play an important role in the sexual dimorphism of HCC [55].…”
Section: Androgen Receptor-mediating Signaling In Hbvrelated Hepatocamentioning
confidence: 99%
“…Ймовірна участь тестостерону у цих процесах підтвер-джується наявністю рецепторів андрогенів у гепатоцитах і холангіоцитах [4][5][6]. Дійсно, кастрація щурів або нейтралізація цирку-люючого тестостерону антитілами зменшує масу печінкових проток, викликає апоптоз холангіоцитів, а замісне його введення перешкоджає їх загибелі [6].…”
Section: вступunclassified